BRAND REJUVENATION STRATEGIES: AN ANTIDOTE OF AGEING BRAND OF OMO DETERGENT SOAP (UNIZIK Journal of Marketing, 2025)
Under the correct conditions, revitalizing a dormant brand can be a very successful tactic. It is widely accepted that growing older is the most welcome change in life. Many businesses have watched their brands loss their relevance over time, and this has dwindled their market share and ultimately, sales revenue. The study examined the effect of brand rejuvenation strategies on marketing performance of Omo detergent soap in Nigeria, using a cross- sectional survey design. The sample population of the study is two hundred (200) respondents from Unilever Nigeria, producer (Omo) detergent. Descriptive and inferential statistics were used to analyse, data collected, while stated hypotheses were tested using multiple regression. The findings revealed that celebrity endorsement, brand innovativeness/creativity and logo have significant influence on marketing performance of Omo. Thus, the authors conclude that for the product to regain its market share, it is imperative that Unilever embarks on aggressive revitalisation of the products quality and strategically re-position the brand in the minds and hearts of the final consumers. The conclusion stated that companies should be more aggressive because it is necessary to change the product attribute and introduce newer products with more uses in order to make the products more marketable. The recommendation of the study suggests that businesses should employ more brandrejuvenating tactics that try to alter consumers' perceptions.
Keywords: Brand Rejuvenation Strategy, Celebrity Endorsement, Brand Innovation/Creativity, Brand Logo and Marketing Performance